Implementation of monitoring for genetically modified rapeseed in Serbia - Nikolic,Zorica (Pontificia Universidad Católica de Valparaíso, 2010)
Genetically modified (GMO) rapeseed (Brassica napus) is not grown commercially in European Union, but several lines have been approved for production and use as food and feed. A case-specific monitoring of herbicide-tolerant rapeseed, events RT73, RF3 and T45 was established by Ministry of Agriculture of Republic of Serbia. The objectives of the present study were to introduce methods for detection of herbicide-tolerant GM oilseed rape, investigate occurrence and monitor the presence of GM rapeseed in seed and the feed products, as well as to develop a protocol for quantification. The study was based on 48 samples, rapeseed (33) and feed (15) products, imported from EU countries (Germany, Belgium, France, Czech Republic, Austria) and from domestic market. Seven positive feed samples and no positive seed samples have found. The percent of GMO in feed samples, estimated on semi-quantitative way, was below labelling threshold. Adventitious presence of GM materials in non-GM grain, derived food and feedstuffs is a concern to international grain trade and needs continuous monitoring.